Infrared spectroscopy of NaCl(CH3OH)n complexes in helium nanodroplets - Sadoon, Ahmed M.; Sarma, Gautam; Cunningham, Ethan M.; Tandy, Jon; Hanson-Heine, Magnus W.D.; Besley, Nicholas A.; Yang, Shengfu; Ellis, Andrew M. (American Chemical Society, 2016)
Infrared (IR) spectra of complexes between NaCl and methanol have been recorded for the first time. These complexes were formed in liquid helium nanodroplets by consecutive pick-up of NaCl and CH3OH molecules. For the smallest NaCl(CH3OH)n complexes where n = 1-3, the IR data suggest that the lowest energy isomer is the primary product in each case. The predominant contribution to the binding comes from ionic hydrogen bonds between the OH in each methanol molecule and the chloride ion in the NaCl, as established by the large red-shift of the OH stretching bands compared with the isolated CH3OH molecule. For n ≥ 4 there is a dramatic shift from discrete vibrational bands to very broad absorption envelopes, suggesting a profound change in the structural landscape and, in particular, access to multiple low-energy isomers.